Probing the Role of Cysteine Thiyl Radicals in Biology: Eminently Dangerous, Difficult to Scavenge - Bernd Moosmann; Parvana Hajieva (MDPI AG, 2022)
Thiyl radicals are exceptionally interesting reactive sulfur species (RSS), but rather rarely considered in a biological or medical context. We here review the reactivity of protein thiyl radicals in aqueous and lipid phases and provide an overview of their most relevant reaction partners in biological systems. We deduce that polyunsaturated fatty acids (PUFAs) are their preferred reaction substrates in lipid phases, whereas protein side chains arguably prevail in aqueous phases. In both cellular compartments, a single, dominating thiyl radical-specific antioxidant does not seem to exist. This conclusion is rationalized by the high reaction rate constants of thiyl radicals with several highly concentrated substrates in the cell, precluding effective interception by antioxidants, especially in lipid bilayers. The intractable reactivity of thiyl radicals may account for a series of long-standing, but still startling biochemical observations surrounding the amino acid cysteine: (i) its global underrepresentation on protein surfaces, (ii) its selective avoidance in aerobic lipid bilayers, especially the inner mitochondrial membrane, (iii) the inverse correlation between cysteine usage and longevity in animals, (iv) the mitochondrial synthesis and translational incorporation of cysteine persulfide, and potentially (v) the ex post introduction of selenocysteine into the genetic code.